Endonuclease‐G and the pathways to dopaminergic neurodegeneration: a question of location?. (25th October 2013) - Hogg, Marion C; Prehn, Jochen H M
<x xml:space="preserve">Abstract</x> Endonuclease‐G and its release from the mitochondria mediates a‐synuclein cytotoxicity.